Development, stability and in vitro permeation studies of gels containing mometasone furoate for the treatment of dermatitis of the scalp (Brazilian Journal of Pharmaceutical Sciences, 2010)
Dermatological inflammatory diseases such as atopic dermatitis, psoriasis and seborrhoeic dermatitis often affect the scalp and the eyebrows. Although there are many dosage forms available, these are particularly critical anatomic regions for application of topical formulations because of the presence of hair. Lotions are therefore the recommended type of drug delivery system for these areas. The presence of hair may limit the application and thus the acceptability of the formulation and its compliance. Because of its low apparent viscosity, lotion application is unpleasant. Gels, given their consistency and adhesiveness, are a suitable alternative to lotions in this situation. The aim of this study was to formulate a stable gel containing mometasone furoate, which is an anti-inflammatory and anti-pruritic corticosteroid, in order to improve topical treatment of scalp dermatitis. In this study, pharmaceutical development, physical-chemical characterization, stability and in vitro permeation studies were performed. In terms of the pH, viscosity, assay and macroscopic and microbiological properties, the gel was stable over the period of study. The in vitro permeation studies allowed the characterization of the mometasone furoate permeation profile for the gel through different membranes. Mometasone furoate presented a slow permeation through the skin. This gel appears safe for topical application.